Long-Term Fishing Catch and Effort Trends in the Republic of the Marshall Islands, With Emphasis on the Small-Scale Sectors - Vianna, Gabriel M. S.; Hehre, E. James; White, Rachel; Hood, Lincoln; Derrick, Brittany; Zeller, Dirk (Frontiers in Marine Science, 2020)
Small-scale fishing has been an important element of the livelihood and food security in Pacific Island countries throughout history; however, such catches have been under-reported in the official fisheries data. Here, we reconstruct the total domestic catches and fishing effort of the Republic of the Marshall Islands (RMI) by fishing sectors for 1950-2017. Reconstructed total catches were estimated to be 27% higher than the data officially reported by the Food and Agriculture Organization of the United Nations on behalf of the RMI. Catches of the truly domestic, but export-oriented, industrial tuna sector accounted for 84% of the total catch, dominating catches since the early 2000s. The subsistence component contributed 74% of total small-scale catches, of which 92% was deemed unreported. The remaining 26% of small-scale catches were artisanal, i.e., small-scale commercial, in nature, of which 45% was deemed unreported. Trends suggested steady growth in small-scale catches from 1,100 t·year-1 in the early 1950s to a relatively stable level of 4,500 t·year-1 since the 1990s. However, over the 2009-2017 period, there was a gradual reduction of 2% per year in subsistence fishing, which was paralleled by a concomitant increase in artisanal catches of 3% per year. This gradual shift from predominantly non-commercial to commercial small-scale fisheries may be related to efforts to commercialize small-scale fisheries in the past decades. Small-scale fishing effort increased approximately 13-fold from the early 1980s to the late 2000s, stabilizing at around 401,000 kWdays since then, while catch-per-unit-of-effort displayed an inverse pattern, declining 8-fold between the 1980s and 1990s, and stabilizing around 15 kg∙kWdays-1 in recent decades. These findings may assist sustainable coastal fisheries management in the RMI, which is particularly important given the increasing impacts of climate change on local stocks.